The evolving use of technology in the South African capital markets - Comninos, Alexis (My University, 2014)
Since the move from floor to electronic trading, technology has played an increasingly important role in the capital markets. Current economic and capital markets developments are driving changes in technology use with several implications for the industry. A series of semi-structured interviews was conducted with participants in the South African capital markets to explore the evolution of technology in the South African capital markets. Key findings are as follows: 1) There is a shifting focus in technology use from cost reduction to competitive advantage 2) Regulatory reforms resulting from the 2008/09 financial crisis are driving increasing use of technology 3) Algorithmic trading and Direct Market Access (DMA) are increasing, but care orders are still a significant part of most brokers’ business 4) High Frequency Trading (HFT) is a niche market and the JSE is pursuing initiatives to grow HFT in the South Africa markets 5) Participants’ views on the impacts of HFT on market quality are mixed 6) Risks of a technology related failure such as the US flash crash are somewhat less in the SA market, but need to be mitigated 7) The increasing use of analytics and big data technologies is potentially one of the next major trends in the capital markets
MBA thesis
Keywords: Johannesburg Securities Exchange; Electronic trading; Information technology